Strategi dan Optimalisasi Peran Human Resources dalam Meningkatkan Employee Engagement pada UMKM D’Sruput Lubuk Begalung Padang - Bunga Henida Putri; Adis Putra Syahditia; Muhammad Abdul Razaq; Muhammad Irvan; Tri Yoma Elsa; Vivi Nila Sari (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting national economic growth, particularly through job creation and strengthening the local economy. However, many MSMEs still face limitations in human resource (HR) management, particularly in enhancing employee engagement. Low employee engagement can impact productivity, service quality, and business profitability. This study aims to analyze strategies and optimize the role of Human Resources (HR) in enhancing Employee Engagement at the D'Sruput Lubuk Begalung Padang MSME. The study employed a qualitative approach with a case study method. Data were collected through direct observation and interviews with the business owner and employees. The results showed that the implementation of two-way communication, flexible work arrangements, employee involvement in simple decision-making, and employee reward and development systems can increase motivation, loyalty, and work commitment. Consistently implemented HR strategies have been shown to play a significant role in strengthening employee engagement and maintaining the competitiveness of MSMEs.